2020
DOI: 10.1021/acs.cgd.9b01230
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and First-Principles Calculations of the Mid-IR Laser Crystal Dy3+:PbGa2S4

Abstract: A Dy3+-doped PbGa2S4 crystal with low phonon energy has been proved to be able to achieve the direct lasing of a mid-infrared laser. The single-crystal growth of Dy3+:PbGa2S4 was investigated in this work. On the basic of the high-purity polycrystalline material synthesized using a pressure-assisted method, a Dy3+:PbGa2S4 single crystal with φ 21 × 50 mm3 was successfully grown using the Bridgman method with a crucible–capsule technique. To understand the cleavage character of the PbGa2S4 crystal and get furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Rare-earth borate is an important optoelectronic functional material for applications in lasers, nonlinear optics, self-frequency doubling, etc. Generally, RE ions have a special 4f n electronic configuration, where the 4f electrons are partially shielded by the outer 5s/5p orbitals . Thus, rare-earth borates usually have a reduced electron–phonon coupling effect compared to transition-metal-doped crystals, such as titanium sapphire and alexandrite. , In order to enhance such a weak coupling effect, we employed the anion-centered polyhedron strategy to evaluate the role of special anion vibrations on the 4f electron transition of a RE ion.…”
Section: Resultsmentioning
confidence: 99%
“…Rare-earth borate is an important optoelectronic functional material for applications in lasers, nonlinear optics, self-frequency doubling, etc. Generally, RE ions have a special 4f n electronic configuration, where the 4f electrons are partially shielded by the outer 5s/5p orbitals . Thus, rare-earth borates usually have a reduced electron–phonon coupling effect compared to transition-metal-doped crystals, such as titanium sapphire and alexandrite. , In order to enhance such a weak coupling effect, we employed the anion-centered polyhedron strategy to evaluate the role of special anion vibrations on the 4f electron transition of a RE ion.…”
Section: Resultsmentioning
confidence: 99%
“…The Pb/Ga/ S ratio was set to 1 : 2 : 4.04 (S-rich) and 1 : 2.02 : 4.04 (PbS : Ga 2 S 3 = 1 : 1.01 with excess 0.01 S, Ga 2 S 3 -rich), respectively. Our previous work 22 demonstrated that the doping concentration of 0.7 atom% led to the precipitation of Dy. Herein, the Dy doping concentration was set at the same 0.5 atom% in each group.…”
Section: Crystal Growthmentioning
confidence: 97%
“…Another case is Dy doping PbGa 2 S 4 . Crystals of Dy 3+ : PbGa 2 S 4 waere grown using the Bridgeman method, 124 and the 21 × 50 mm 3 size Dy 3+ : PbGa 2 S 4 single crystals could obtained.…”
Section: Crystal Growth For Lone-pair Cation-based Ir Nlo Materialsmentioning
confidence: 99%